Influence of Salt Anions on the Reactivity of Polymer Electrolytes in All-Solid-State Sodium Batteries. Issue 7 (1st July 2022) - Peta, Gayathri; Alon-Yehezkel, Hadas; Bublil, Shaul; Penki, Tirupathi Rao; Breuer, Ortal; Elias, Yuval; Fayena-Greenstein, Miryam; Aurbach, Doron
Abstract : Solid-state batteries have received renewed attention in recent years. The present study compares all-solid-state sodium batteries containing sodium metal anodes, NaTi2 (PO4 )3 (NTP) cathodes and PEO polymer electrolyte (PE) with two salts—NaPF6 and NaClO4 . Electrochemical properties were determined by means of both AC and DC measurements. For fresh symmetric cells, it seems like using NaClO4 as the salt leads to a lower interfacial resistance, but during contact with Na anodes, PEO:NaClO4 PE produces an unstable interface whereas PEO-NaPF6 forms a stable interface upon contact with sodium anodes. Battery prototypes with PEO:NaClO4 showed a better performance than those using PEO:NaPF6 in terms of specific capacity and energy content, as NaPF6 produces HF by-product which impairs the performance of full cells. However, the use of composite solid electrolyte containing PEO:NaPF6 and TiO2 nanotubes alleviates detrimental effects of HF and thus enables a better performance of SS Na battery prototypes. This is probably due to the titania particles acting as a scavenger of HF, an inevitable contaminant in electrolyte systems containing PF6 − anions. On adding TiO2 to polymer electrolytes, of both salts, the performance improves, what means that the TiO2 has several positive effects in these systems.